Pengembangan Desain Interaktif 3D VR-Room Patient Menggunakan Unity 3D Engine Dan Evaluasi Usability Testing - Rizqi Putri Nourma Budiarti; Fajar Annas Susanto; Bayu Riskiananto; Paramitha Nerisafitra (Jurnal Ilmiah Informatika, 2019)
The development of Virtual Reality technology is currently being developed even in every field of science, one of which is room mapping. Mapping digital space as a visualization medium has helped provide detailed information through the use of three-dimensional (3D) technology. To build a visualization of the room that is useful for the community, especially in the area of ​​the hospital environment, especially hospital patients so that in fighting the disease patients remain in a state of enthusiasm, safe, comfortable and conducive supported by the environment. With the use of 3D technology, in building an interactive room design VR-Room Patient using the Unity 3D Engine is expected to help patients in choosing treatment rooms for Inpatient Hospital. The planned room description is the Presidential Suite Room, Deluxe Suite, Junior Suite and Class II. The results of this study in the form of visualization illustrated by each area, while the evaluation of the results of this study was conducted by asking respondents to fill in an assessment questionnaire on VR visualization using usability testing using the usability heuristic approach, and the usability test results obtained with an average value of 3.194 taken from the assessment of respondents on a scale of 1 to 4 where this explains that the VR-Room Patient application has a good level of reusability ie the average value is above 3.